El presente histórico del movimiento indígena boliviano : evidenciando la latencia histórica (2017)
The historical present can be explained since the conception of a historical latency, that means the past manifest it self in the present. This work studies the historical presnet of the indigenous social movement aymara in Bolivia since their historical latency, trying to approach to the complex understanding of this social actor.